EDUKASI EFEK BIOLOGI RADIASI DI DESA KARANGSUNO KECAMATAN CEPIRING KABUPATEN KENDAL - Andriani, Intan; Suraningsih, Nanik (Pusat Penelitian dan Pengabdian Masyarakat, 2025)
Knowledge about the dangers of radiation during radiological examinations remains low among the people of Karangsuno village, Cepiring sub-district, Kendal district. Therefore, education is necessary for the community to minimise biological effects. The Community Service team provides information on radiation dangers that need to be known and what can be done when in the vicinity of X-ray radiation sources. The Community Service team will employ a method that involves administering a pre-test, providing education, and administering a post-test. The results of the community service activities conducted on Saturday, June 14, 2025, at Karangsuno village, Cepiring sub-district, Kendal district, show that the residents have understood the material provided. This is indicated by an increase in knowledge after the education session regarding radiation dangers, radiation protection, and the application of personal protective equipment (PPE) during radiological examinations[1].